Importance of controlling the degree of saturation in soil compaction linked to soil structure design - Tatsuoka, Fumio (2018)
In the typical conventional fill compaction, the dry density, ρd, and the water content, w, are controlled in relation to reference values, (ρd)max and wopt, determined by standard laboratory compaction tests using a representative sample at a certain compaction energy level, CEL. Although CEL and soil type affect significantly (ρd)max and wopt, they change inevitably, sometimes largely, in a given earthwork project while field CEL may not match the value used in the laboratory compaction tests. Compaction control based on only an index of strength/stiffness of compacted soil has such a drawback that, for a fixed value of ρd, the index may increase significantly as the degree of saturation, Sr, of compacted soil becomes lower than the optimum degree of saturation (Sr)opt defined as Sr when (ρd)max is obtained for a given CEL. In comparison, the value of (Sr)opt and the unified compaction curve in terms of ρd/(ρd)max vs. Sr−(Sr)opt relation of compacted soil are rather insensitive to variations in CEL and soil type. Besides, CBR (unsoaked and soaked), the unconfined compression strength, the elastic shear modulus and the collapse upon submerging of compacted soil and the cyclic undrained shear strength and the coefficient of hydraulic conductivity of saturated soil are all controlled by ρd and “Sr at the end of compaction”. As a standard method, it is proposed to control the values of w and ρd in such that Sr becomes (Sr)opt while ρd becomes large enough to ensue soil properties required in design fully taking advantage of available CEL. It is argued that the compaction control keeping Sr larger than a certain value (or the air void ratio va lower than a certain value) without controlling ρd is relevant as a simplified method only if Sr is controlled to become (Sr)opt while always keeping CEL high enough to ensure the soil properties required in design.